Exposure‐Response Model of Subcutaneous C1‐Inhibitor Concentrate to Estimate the Risk of Attacks in Patients With Hereditary Angioedema. (9th January 2018) - Zhang, Ying; Tortorici, Michael A.; Pawaskar, Dipti; Pragst, Ingo; Machnig, Thomas; Hutmacher, Matthew; Zuraw, Bruce; Cicardi, Marco; Craig, Timothy; Longhurst, Hilary; Sidhu, Jagdev
Abstract : Subcutaneous C1‐inhibitor (HAEGARDA, CSL Behring), is a US Food and Drug Administration (FDA)‐approved, highly concentrated formulation of a plasma‐derived C1‐esterase inhibitor (C1‐INH), which, in the phase III Clinical Studies for Optimal Management in Preventing Angioedema with Low‐Volume Subcutaneous C1‐inhibitor Replacement Therapy (COMPACT) trial, reduced the incidence of hereditary angioedema (HAE) attacks when given prophylactically. Data from the COMPACT trial were used to develop a repeated time‐to‐event model to characterize the timing and frequency of HAE attacks as a function of C1‐INH activity, and then develop an exposure–response model to assess the relationship between C1‐INH functional activity levels (C1‐INH(f)) and the risk of an attack. The C1‐INH(f) values of 33.1%, 40.3%, and 63.1% were predicted to correspond with 50%, 70%, and 90% reductions in the HAE attack risk, respectively, relative to no therapy. Based on trough C1‐INH(f) values for the 40 IU/kg (40.2%) and 60 IU/kg (48.0%) C1‐INH (SC) doses, the model predicted that 50% and 67% of the population, respectively, would see at least a 70% decrease in the risk of an attack.